2019
DOI: 10.14203/treubia.v45i0.3109
|View full text |Cite
|
Sign up to set email alerts
|

On Skeletochronology of Asian grass frog Fejervarya limnocharis (Gravenhorst, 1829) from Java to support management conservation

Abstract: Asian grass frog Fejervarya limnocharis is being utilized as pets, for laboratory experiments, for a mixture of traditional medicine and for cuisine. The harvest of F. limnocharis in high volume can threat its population. Biological data such as the age when the specimens are harvested is valuable information to manage the harvesting system in sustainable way. We conducted the skeletochronology technique using paraffin methods and hematoxylin staining from 69 samples (46 males, 21 females, 2 juveniles). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Skeletochronology technique was successfully applied for femur bone of F. cancrivora, which improved the results that had been done by Kusrini and Alford (2006) for the same species. The success of the skeletochronology technique also proved in F. limnocharis (Liao et al 2011;Pancharatna and Deshpande 2003;Phadmacanty et al 2018) which is a close relative to F. cancrivora. The number of LAG compared with the length of SVL at the pre-adult stage, adult males and adult females showed accurate results with a strong correlation between the two parameters.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Skeletochronology technique was successfully applied for femur bone of F. cancrivora, which improved the results that had been done by Kusrini and Alford (2006) for the same species. The success of the skeletochronology technique also proved in F. limnocharis (Liao et al 2011;Pancharatna and Deshpande 2003;Phadmacanty et al 2018) which is a close relative to F. cancrivora. The number of LAG compared with the length of SVL at the pre-adult stage, adult males and adult females showed accurate results with a strong correlation between the two parameters.…”
Section: Discussionmentioning
confidence: 87%
“…A preliminary study of Indonesian frog age by using skeletochronology on F. cancrivora, F. limnocharis and Limnonectes macrodon were done by Kusrini and Alford (2006) They reported that the maximum number of LAGs (Line of Arrested Growth) from 35 samples (SVL=14.5-56.7 mm) F. cancrivora was one. The results of skeletochronological research which was conducted by Phadmacanty et al (2018) for F. limnocharis found varied number of LAGs, so did the Pancharatna and Dehpande (2003) result, while Kusrini and Alford (2006) also only found one LAG on 103 samples (SVL=15.68-53.00 mm).…”
Section: Introductionmentioning
confidence: 91%
“…False lines, which may form during an unfavorable period in summer, are generally fainter than LAGs and do not form a complete ring around the bone section. We counted double lines in cross‐sections as 1 year of age; thus, they cannot affect the LAGs counted (Iturra‐Cid et al., 2010 ; Jiang et al., 2022 ; Khaloei et al., 2023 ; Phadmacanty et al., 2019 ; Yuan et al., 2021 ; Zhang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In general, life cycles of rice frogs includes several stages, i.e., egg, tadpole, froglet, juvenile, sub-adult, and adult (Duellman and Trueb, 1994), where abundances may vary according to season and water availability. Based on previous skeletochronological studies, it was reported that the natural lifespan of F. limnocharis in Southern India can reached up to 4 years in both sexes (Pancharatna and Deshpande, 2003), slightly different from the subtropical F. limnocharis in China, which had a lifespan of 3 years old for males and 4 years old for females (Liao et al, 2011), and slightly longer from tropical F. limnocharis from Indonesia, which reached maximum age of 3 years with maximum SVL of 52.37 mm (Phadmacanty et al, 2019). These differences are attributed to many factors such as habitat, altitude, and environmental condition.…”
Section: Figure 27mentioning
confidence: 99%